Decisión making and decisión support systems for balancing Socio-Economic and Natural Capital Development. - Vadineanu, Angheluta (Observatorio Medioambiental, 2001)
The paper discusses briefly a hierarchical spatio-temporal framework to study globalization, economics and ecology for better understanding and conceptualization of the balance between biodiversity and Natural Capital (NC) on one side, and the Socio-Economic Systems (SES), on the other side, which was designed based on the recent achievements in the field of Systems Ecology. Based on the conceptual clarification of the dynamic condictions for sustainability and on an extensive review of the most recent literature, there are proposed and discussed the decision support system and decision making model as the operational interface between Natural Capital components and Socio-Economic Systems, which might enable to establish and maintain the balance among them. The identified weaknesses and gaps in the structure and function of the Decision Support System (DSS) show the need for extensive and long term research and integrated monitoring and for development and improvement of the methodology and tools.